Proceso de atención de enfermería a escolar de 7 años con cardiopatía chagasica. - Manrique Medrano, Karla Melissa (2021)
The present clinical case was performed in a 7-year-old male patient with chagasic heart disease, which is related to Chagas disease (CHD) or American trypanosomiasis, which is transmitted by a hematophagous insect in urban areas and rural. The Pan American Health Organization states that between 7.7 and 10 million people have a chronic infection and most of them are unaware that they suffer from said infection, due to this, CHD has been described as a disease of little importance. It is a tropical parasitic disease, caused by the flagellated protozoan Trypanosoma cruzi (T. cruzi), the same one that affects the cardiovascular, digestive and nervous systems, among the most common pathologies cardiac alterations. This parasite is capable of being transmitted through the mother-to-fetus route, and there are also reports of cases of infection by blood transfusions. In this clinical case, our objective is to present the rare case of a school-age patient with early cardiac manifestations of CHD and to analyze the relevance of entomological surveillance in his environment, as an epidemiological surveillance measure applied to the entire population.